Trophic niche adaptation of mountain frogs around the Sichuan Basin: individual specialization and response to climate variations - Kaiyue Cui; Shengnan Yang; Junhua Hu (Frontiers in Zoology)
Abstract Background Climatic and geographic variations have profound effects on the resource utilization of individuals and populations. Evaluating resource use in different environments is crucial for understanding species ecological adaptation strategies and promoting biodiversity conservation. Stable isotopes are widely used to assess trophic niches, providing quantitative indicators of ecological interactions between organisms and resource use in ecosystems. This study assesses the trophic niche traits of spiny-bellied frogs (Quasipaa boulengeri) in the marginal mountains of the Sichuan Basin in southwestern China using stable isotopes. Trophic niche variation under different time periods and environmental conditions is explored. Results The spiny-bellied frogs experienced a significant reduction in trophic niche width during the past breeding season. The populations in the northwestern Sichuan Basin had a greater trophic niche width than the southeastern populations, and their δ15N values showed a positive correlation with temperature seasonality and a negative correlation with annual precipitation. Despite differences between the northwestern and southeastern populations, there was a consistent trend of increased individual specialization with latitude in both the northwestern and southeastern regions. Conclusions Ontogenetic niche shifts and differences in trophic niche traits between the northwestern and southeastern populations indicate diverse adaptation strategies in mountain frogs. The findings underscore the impact of geographical and climate variations on the resource utilization of amphibians. In addition, patterns of individual specialization highlight the significance of considering intra- and interpopulational changes when studying ecological adaptation.